Sulla storia degli studi di frattura in Italia - Roberto L. Colombo; Donato Firrao (Fracture and Structural Integrity)
History of studies of fracture is inherently intermingled with the history of technology developments. In the beginning very little was written about. We must credit Leonardo and Galileo as the first ones that wrote about the problem and on how to measure and foresee rupture loads. Later, nineteenth century italian scientists distinguished themselves in attempting to establish material laws and multiple stresses rupture criteria. A review of the works of past centuries italian scientists is presented, along with a critical comparison with the work of other past european scientists.